Pulmonary Pyoseptic Complications in Severe Concomitant Injury: Prevention and Intensive Care - Ye. A. Kameneva; S. S. Koval; Ye. V Grigoryev; A. S. Razumov; O. N. Yegorova (Общая реаниматология)
Objective: to enhance the efficiency of intensive therapy and prevention of pyoseptic complications (PSC) of severe concomitant injury. Subjects and methods: A hundred patients who were divided into three groups were examined. A control group consisted of 30 apparently healthy individuals (donors). A study group comprised 38 patients to whom the standard of intensive care and prevention of PSC of severe concomitant injury was applied. A comparison group included 32 patients who received specific preventive therapy for pulmonary PSC, by incubating the cell mass with recombinant interleukin-2. Hemostatic parameters were followed up by biochemical tests and hemoviscosimetry. Immunological parameters, the data of semiquantitative procalcitonin test, and the clinical laboratory parameters of a systemic inflammatory response, as well as complications were analyzed. Results. In the intervention group, the signs of a systemic inflammatory response regressed beginning on day 2 of therapy, the results of the procalcitonin test and vascular thrombocytic hemostasis became normal and the time of respiratory support and the length of intensive care unit stay reduced. Conclusion. The early combination of cell mass with recombinant interleukin-2, beginning on day 2 of therapy for severe concomitant injury, enhances the efficiency of intensive therapy and prevention of pulmonary PSC. Key words: severe concomitant injury, infectious complications, diagnosis, recombinant interleukin-2.